Depression literacy, mental health literacy, and their relationship with psychological status and quality of life in patients with type 2 diabetes mellitus - Jafari, Alireza; Moshki, Mahdi; Naddafi, Fatemehzahra; Ghelichi-Ghojogh, Mousa; Armanmehr, Vajihe; Kazemi, Kimia; Nejatian, Mahbobeh (Frontiers in Public Health, 2024)
Background: This study was conducted with the aim of measuring depression literacy (D-Lit), mental health literacy (MHL), and investigating their relationship with psychological status and quality of life among Iranian patients with type 2 diabetes mellitus (T2DM). Methods: This cross-sectional study was conducted in 2021 among 400 patients with T2DM in Iran. Samples were selected using proportional stratified sampling. The data collection instruments comprised a demographic questionnaire, MHL, D-Lit, diabetes quality of life (DQOL), and DASS-21.After confirming the normality of the data using the Kolmogorov-Smirnov test, parametric statistical tests (One-way ANOVA, Independent samples t-test, and Chi-Square) were used to investigate the relationship between the variables using SPSS v22 software. The results of continuous quantitative data are reported in the form of mean and standard deviation, and qualitative data are reported in the form of absolute and relative frequency. Results: In this study, 10.3 % (n=41) had severe depression and 36.18 % (n=147) had severe anxiety. The mean (standard deviation) of MHL was 80.92 (9.16) from 145. Of the participants, only 1.8 % (n=7) did not answer any questions correctly on the D-lit, and only 5.8 % (n= 23) were able to answer 15 questions and more correctly on the D-lit. MHL had a negative significant correlation with depression (r=-0.236), anxiety (r=-0.243), and stress (r=-0.155) (P <0.001). There was a positive and significant correlation between MHL and D-Lit (0.186) (P<0.05). D-Lit had a negative significant correlation with depression (-0.192), anxiety (-0.238), and stress (-0.156) (P <0.001). There was a positive and significant correlation between the ability to recognize disorders (0.163) and knowledge of self-treatment (0.154) and DQOL (P<0.001). Depression (r=-0.251), anxiety (r=-0.257), and stress (r=-0.203) had a significant negative correlation with DQOL (P <0.001). Conclusion: MHL and D-Lit levels were inadequate in patients with T2DM. Low levels of MHL and D-Lit among patients with T2DM were associated with higher levels of anxiety, depression, and stress and lower quality of life. Therefore, designing and implementing preventive programs to improve the mental health of patients with T2DM can help prevent mental disorders and ultimately improve their quality of life